The influence of group affiliation and the underwriting process on emerging market IPOs: The case of the Philippines - Sullivan, Michael J. (Animo Repository, 2001)
In this paper we document underpricing and aftermarket returns of Philippine IPOs, discuss specific features of the Philippine IPO market, and investigate whether differential underpricing occurs due to certification considerations or potential conflicts of interest. We find that IPO underpricing is greater in cases where the offering firm is affiliated to a family business group, specifically when these affiliated firms use a foreign lead underwriter. Our results lead us to conclude that conflict of interest problems are recognized by market participants and that these conflicts of interest lead to differential underpricing. © 2001 Elsevier Science B.V.